An inventory of gender-related research and training in the Consultative Group on International Agricultural Research (CGIAR) Centers - Feldstein, H (CGIAR System Organization, 1998)
In 1995, the CGIAR Gender Analysis Program published the first inventory of gender-related research, training, and information dissemination activities. This second inventory takes us from 1996 to 1998.